PERFORMANCE ANALYSIS OF WAQF INSTITUTION USING BALANCED SCORECARD ANALYSIS: CASE STUDY AT LAZNAS YATIM MANDIRI (IAIN Tulungagung, 2022)
This research aims to measure the performance of the waqf institution (LAZNAS Yatim Mandiri) using a balanced scorecard (BSC). This study uses quantitative and qualitative analysis or mixed-method by using a balanced scorecard (BSC). The Balanced Scorecard is used to measure performance from both a financial perspective and a non-financial perspective, which includes four main perspectives: (1) finance, (2) customers, (3) internal business processes, and (4) learning and growth. The study found that an overall BSC score of 85,6% shows that the performance of LAZNAS Yatim Mandiri is categorized as very good. From each perspective, customer perspective is the highest BSC score, followed by financial perspective and internal business while learning and growth perspective gain the lowest score. The BSC suggests a direction of priority to improve each strategic goal of perspective. Customer satisfaction becomes the first place, followed by waqf collection and distribution as the second priority. The next priority is employee satisfaction while keeping other strategic goals to be maintained. The findings of this study could help Islamic philanthropic institutions define their vision and strategy, as well as change their vision and strategy into specific activities, by implementing measures that are accurate and comprehensive, as well as providing information that is accurate and correct for managers to make business decisions.